Asmaul husna Sebagai Sumber Etika Islam serta Implementasinya dalam Kehidupan - Muhammad Isrha; Hamzah Harun; Indo Santalia (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This discussion addresses Asmaul Husna as a source of Islamic ethics and its implementation in life, including the meaning of Asmaul Husna itself, Asmaul Husna as a source of guidance for ethics in Islam, and how it is implemented in daily life. The foundation of ethics in Islam is guided by the names of Asmaul Husna, which possess meanings that encompass all human behavior. Asmaul Husna functions as a moral and ethical guide, providing values that can be applied in everyday life. The method used in this article is an in-depth literature review, analyzing classical and contemporary texts related to Asmaul Husna. The conclusion of this discussion shows that a deep understanding of Asmaul Husna is not only important for strengthening faith, but also crucial in shaping strong and ethical character, especially amid modern challenges such as secularism and relativism.